First Generation Solar Cell: History And Development Of Silicon-Based Photovoltaics - Gultom, Noto Susanto; Sugandi, Adinda A. Nur; P. Dewi, Aisyah; Qulsum, Kirana; Elisabet, Mona; Aprillia, Bandiyah Sri; Hidayat, Sahrul; Nilam, Putri Nuri; Simanjuntak, Mayer (Universitas Padjadjaran, 2025)
The global transition toward new and renewable energy sources to address environmental issues and the limitations of conventional energy reserves remains a priority. Solar energy, through photovoltaic technology, emerges as a promising option for mitigating the environmental impact of traditional energy. The fact that solar energy is a sustainable resource and a viable means to reduce reliance on fossil fuels supports this. Solar cells are devices made from semiconductor materials capable of converting solar energy into electrical energy. We categorize first-generation solar cells into silicon monocrystalline, silicon polycrystalline, and III- V single junctions based on GaAs. This article reviews the characteristics of first-generation silicon-based solar panels, including efficiency, light absorption, and transmission, which dominate the global market. This review aims to provide an in-depth understanding of the factors influencing the performance of silicon-based solar cells, which will contribute to the development and application of solar cell technology in the future. Keywords: solar energy, solar cell, silicon, monocrystalline, polycrystalline